Indigenous and Non-Indigenous Unemployment, Employment, and Participation Rates Through 2023: Education Remains Critical - Oppenheimer, Robert (Journal of Aboriginal Economic Development, 2024)
Employment, unemployment, participation, and wage rates have been more favourable for the non-Indigenous population than for the Indigenous population. With one exception, this has been the case in every year since 2007, when the data first became available. While wages were higher in 2022 than they were in 2021 for both Indigenous and non-Indigenous populations, the overall employment picture for the Indigenous population was worse in 2023 than in 2022. Their unemployment rate was higher, while their employment and participation rates were lower. In comparison, all three rates were higher for non-Indigenous people in 2023. A critical factor related to each of these three rates is the education level achieved. Higher completed educational levels are directly related to lower unemployment rates and higher employment and participation rates as well as to higher wage levels.